Major risk factors for stillbirth in different trimesters of pregnancy-A systematic review - Li-Chun Liu; Yu-Chi Wang; Mu-Hsien Yu; Her-Young Su (Elsevier, 2014)
Stillbirth remains an event that has an important impact on global health issues. Different levels of health care between countries suggest that the stillbirth rate may be one of the indicators of the quality of a country's medical system. In this review, major risk factors for stillbirth will be discussed, especially in different trimesters of pregnancy. Early identification of risk factors for stillbirth and appropriate antenatal management may reduce preventable stillbirths and improve general outcomes of pregnancy.